PENGARUH MODEL TALKING STICK BERBANTUAN MEDIA KACIMA TERHADAP HASIL BELAJAR IPA MATERI CIRI MAKHLUK HIDUP SISWA KELAS IV SDN 066053 MEDAN TAHUN AJARAN 2025/2026 - Nur Hayati Hasibuan; Lala Jelita Ananda; Imelda Free Unita Manurung; Fajar Sidik Siregar; Yusra Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low science learning outcomes of elementary school students, particularly on the topic of characteristics of living things. Based on preliminary observations at SDN 066053 Medan Denai, most fourth-grade students had not yet achieved the Minimum Learning Mastery Criteria (KKTP). This condition is influenced by conventional learning practices in which students tend to be passive during the learning process. Therefore, this study aimed to analyze the effect of the Talking Stick learning model assisted by KaCiMa (Characteristics of Living Things Cards) media on the science learning outcomes of fourth-grade students. This research employed a quantitative approach with a quasi-experimental design using the nonequivalent control group design. The population consisted of all fourth-grade students at SDN 066053 Medan Denai in the 2025/2026 academic year, totaling 44 students. The sample included two classes, namely class IV-B as the experimental class that applied the Talking Stick learning model assisted by KaCiMa media and class IV-A as the control class that used the Snowball Throwing learning model. Data collection techniques included observation, interviews, tests, and documentation. The research instrument consisted of 25 multiple-choice test items that had been tested for validity, reliability, difficulty level, and discrimination power. Data analysis was conducted using the Shapiro–Wilk normality test and hypothesis testing using the Wilcoxon Signed Rank Test. The results showed that the application of the Talking Stick learning model assisted by KaCiMa media had a significant effect on improving students’ science learning outcomes on the topic of characteristics of living things.